Perception of faces in schizophrenia: Subjective (self-report) vs. objective (psychophysics) assessments. (May 2016) - Chen, Yue; Ekstrom, Tor
Abstract: Objectives: Face perception impairment in schizophrenia has been demonstrated, mostly through experimental studies. How this laboratory-defined behavioral impairment is associated with patients' perceptual experience of various faces in everyday life is however unclear. This question is important because a first-person account of face perception has direct consequences on social functioning of patients. In this study, we adapted and administered a self-reported questionnaire on narrative perceptual experience of faces along with psychophysical assessments of face perception in schizophrenia. Methods: The self-reported questionnaire includes six rating items of face-related functioning in everyday life, providing a subjective measure of face perception. The psychophysical assessment determines perceptual threshold for discriminating different facial identities, providing an objective measure of face perception. Results: Compared to controls (n = 25), patients (n = 35) showed significantly lower scores (worse performance) in the subjective assessment and significantly higher thresholds (worse performance) in the objective assessment. The subjective and objective face perception assessments were moderately correlated in controls but not in patients. The subjective face perception assessments were significantly correlated with measurements of a social cognitive ability (Theory of Mind), again in controls but not in patients. Conclusion: These results suggest that in schizophrenia the quality of face-related functioning in everyday life is degraded and the role that basic face discrimination capacity plays in face-related everyday functioning is disrupted.